Dari Direct Selling ke Digital Branding: Strategi Pemasaran UMKM “ Bakpia Oma Dian” di Era Digital - Dewi, Liana; Susanti, Liana Dewi; Ilmi, Ulul; Yusuf, M Fajar Baharudin; Kurniawati, Mutiara; Asih, Murni (Adzkiya : Jurnal Hukum dan Ekonomi Syariah, 2025)
Marketing plays a crucial role in ensuring business sustainability amid increasingly intense competition. This study aims to analyze the marketing strategy transformation from direct selling to digital branding at the MSME Bakpia Oma Dian located in Tanggulangin Village, Punggur District. The research employs a Participatory Action Research (PAR) approach, which integrates the research process with social transformation through three main strategies: collective commitment with the community, the involvement of local leaders, and the establishment of community-based institutions. The findings reveal that the digital branding strategies implemented include improving product quality, innovating flavors and packaging, setting affordable prices, choosing strategic business locations, and promoting products through social media platforms such as WhatsApp, Facebook, and Instagram. This transformation has successfully enhanced competitiveness and strengthened the brand image of Bakpia Oma Dian in the digital era. Keywords: Direct Selling, Digital Branding, Marketing Strategy, MSME, Digital Era.